Religion, Institutions and Society in Ancient Rome - John Scheid (Collège de France, 2013)
By opposing sectarian discourses with the universal weapons of history, philology and anthropology, in short, the entire arsenal of science and reason, the history of religions of the past enables us to deflate modern myths, and not only those of others but also our own. It allows us to identify the projection, in the imaginary past, of the "origins" of nationalist, religious or racist fantasies, and to disarm exaggerated interpretations of the sacred texts. Within nations inherited from the ...